The appropriateness of the helical axis technique and six available cardan sequences for the representation of 3-D lead leg kinematics during the fencing lunge - Sinclair, J.; Taylor, P. J.; Bottoms, L. (Journal of Human Kinetics, 2013)
Cardan/Euler angles represent the most common technique for the quantification of segmental rotations. Cardan angles are influenced by their ordered sequence, and sensitive to planar-cross talk from the dominant rotation plane, which may affect the angular parameters. The International Society of Biomechanics (ISB) currently recommends a sagittal, coronal, and then transverse (XYZ) ordered sequence, although it has been proposed that when quantifying non-sagittal rotations this may not be the most appropriate technique. This study examined the influence of the helical and six available Cardan sequences on lower extremity three-dimensional (3-D) kinematics of the lead leg during the fencing lunge. Kinematic data were obtained using a 3-D motion capture system as participants completed simulated lunges. Repeated measures ANOVAs were used to compare discrete kinematic parameters, and intraclass correlations were also utilized to determine evidence of planar crosstalk. The results indicate that in all three planes of rotation, peak angle and range of motion angles using the YXZ and ZXY sequences were significantly greater than the other sequences. It was also noted that the utilization of the YXZ and ZXY sequences was associated with the strongest correlations from the sagittal plane, and the XYZ sequence was found habitually to be associated with the lowest correlations. It appears that for accurate representation of 3-D kinematics of the lead leg during the fencing lunge, the XYZ sequence is the most appropriate and as such its continued utilization is encouraged.